(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the professional competence of a future teacher that is considered as a level of the professional successfulness. It is detailed the interrelations and difference of professional competence of a future teacher with qualification, professionalism and craftsmanship. The diagram of teacher’s professional successfulness is proposed in which the professional competence of a future teacher belongs to the intermediate level.